Diagnosis and Prevention of Scabies in Low Mobility Patients with Cognitive Impairment - T. A. Gaydina; A. S. Dvornikov; O. Yu. Milushkina; A. A. Gamidova (Архивъ внутренней медицины)
Scabies is an infectious skin disease caused by the human-specific ectoparasite Sarcoptes scabiei var. hominis. Despite the comprehensive study of scabies, the problem of its timely diagnosis in low-mobility patients with neurological and cognitive impairments remains relevant all over the world. Simultaneous administration of a large number of medications to patients with limited mobility may mask the clinical manifestations of scabies and mistakenly attribute itching to manifestations of skin allergic reactions or other dermatoses. The authors observed patient K., who was admitted in FCBRN of FMBA of Russia from 14.11.2022 to 15.11.2022. Clinical diagnosis upon admission: I69.3. The consequences of a stroke. Early recovery period of ischemic stroke in the basin of the left middle cerebral artery from 09.08.2022, atherothrombotic subtype according to TOAST criteria. Right-sided hemiparesis. Gross aphasia. Violation of the pelvic organs function. RMS 5. Comorbid diseases: arterial hypertension, controlled, the risk of CVE 4 (very high). The target blood pressure is less than 135/85 mmHg. Occlusion of the left anterior cerebral artery, middle cerebral artery. Toxic-allergic dermatitis (medicinal) in the acute phase. Based on a set of clinical data and laboratory detection of the pathogen, patient K. was diagnosed with B86 — scabies. Even though the patient was under medical supervision at the ambulatory step, scabies was not diagnosed timely. Late diagnosis of scabies leads to the spread of the disease and an unfavorable epidemiological situation.